Uji Validitas dan Reliabilitas Instrumen Penelitian Pemahaman Konsep Biologi - Ina Marthiani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Research instrument is a tool used to collect data or measure objects of a research variable. To obtain accurate data for appropriate conclusions reflecting the actual situation, a valid, consistent, and reliable instrument is required. The validation test of the biology concept comprehension instrument in this research uses the Pearson Product Moment formula and examines the interpretation of its correlation index with the total score. The reliability measurement of the biology concept comprehension instrument uses Cronbach’s alpha formula. The instrument testing is conducted on 30 respondents who are 10th-grade high school students.